2022
DOI: 10.1155/2022/8619092
|View full text |Cite|
|
Sign up to set email alerts
|

The Levels of TNF-α, Tissue Factor, and Coagulation Function in Rats with Pulmonary Hypertension and the Intervention Effect of Sildenafil Encapsulated by Targeted Nanocarriers

Abstract: Pulmonary hypertension (PAH) is a proliferative disease of pulmonary blood vessels, but the pathogenesis of pulmonary hypertension is still unclear. This article explores the role of tumor necrosis factor-α (TNF-α), tissue factor (TF), and coagulation function (CF) in the pathogenesis of PAH. PAH is often accompanied by vascular intima injury and muscular arterial media thickening. Coupled with the wide application of nanotargeted drugs in recent years, a targeted nanocarrier encapsulating sildenafil was prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…TNF‐α can also promote thrombosis by promoting the shedding of protein C receptor, inhibiting the production of thrombomodulin, inducing complement activation, stimulating endothelial cells, and mononuclear phagocytes to produce tissue factors, resulting in an imbalance of the coagulation system 35 . Previous study showed that the elevated levels of serum TNF‐α were closely related to the pathophysiological process of PH 36 . And we present evidence for increased of serum TNF‐α in APMTE rats.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…TNF‐α can also promote thrombosis by promoting the shedding of protein C receptor, inhibiting the production of thrombomodulin, inducing complement activation, stimulating endothelial cells, and mononuclear phagocytes to produce tissue factors, resulting in an imbalance of the coagulation system 35 . Previous study showed that the elevated levels of serum TNF‐α were closely related to the pathophysiological process of PH 36 . And we present evidence for increased of serum TNF‐α in APMTE rats.…”
Section: Discussionmentioning
confidence: 55%
“…35 Previous study showed that the elevated levels of serum TNF-α were closely related to the pathophysiological process of PH. 36 And we present evidence for increased of serum TNF-α in APMTE rats. The results suggested TNF-α levels had important value for closely monitoring development of PH and antiinflammatory therapies may help achieve positive outcomes in PH.…”
Section: Mapk/nf-κb Signaling Activity Was Activated In Apmtementioning
confidence: 60%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%